2018
DOI: 10.3390/w10111549
|View full text |Cite
|
Sign up to set email alerts
|

Improved Process Representation in the Simulation of the Hydrology of a Meso-Scale Semi-Arid Catchment

Abstract: The variability of rainfall and climate, combined with land use and land cover changes, and variation in geology and soils makes it a difficult task to accurately describe the key hydrological processes in a catchment. With the aim to better understand the key hydrological processes and runoff generation mechanisms in the semi-arid meso-scale Kaap catchment in South Africa, a hydrological model was developed using the open source STREAM model. Dominant runoff processes were mapped using a simplified Height Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…tional contributions from the deep aquifer potentially augment baseflow volumes provided by the shallow aquifer and are in accordance with other studies in the region(Saraiva Okello et al, 2018) as well as the broader region of South Africa(Van Tol et al, 2020).In general, the calibrated model simulated far higher overland flow with values of270, 214, 230, 209, and 170 mm compared to uncalibrated model with values of 105, 135 173, 136, and 106 mm, respectively. The same was also true for average annual lateral flow F I G U R E 4 Monthly simulated streamflow for the Hydrosol model runs compared to observed streamflow at (a) X3H003, (b) X3H002, (c) X3H001, (d) X3H024, (e) X3H021 together with (f) the average monthly rainfall.…”
supporting
confidence: 90%
“…tional contributions from the deep aquifer potentially augment baseflow volumes provided by the shallow aquifer and are in accordance with other studies in the region(Saraiva Okello et al, 2018) as well as the broader region of South Africa(Van Tol et al, 2020).In general, the calibrated model simulated far higher overland flow with values of270, 214, 230, 209, and 170 mm compared to uncalibrated model with values of 105, 135 173, 136, and 106 mm, respectively. The same was also true for average annual lateral flow F I G U R E 4 Monthly simulated streamflow for the Hydrosol model runs compared to observed streamflow at (a) X3H003, (b) X3H002, (c) X3H001, (d) X3H024, (e) X3H021 together with (f) the average monthly rainfall.…”
supporting
confidence: 90%
“…Looking in the literature if these KGE values are within the accepted boundaries, we find different limits. Saraiva Okello, Masih, Uhlenbrook, Jewitt, and Van der Zaag (2018) considered values of KGE less 0.5 as poor , between 0.5 and 0.7 as acceptable and above 0.7 as good . Poméon, Diekkrüger, and Kumar (2018) and Rajib, Merwade, and Yu (2016) considered as acceptable models with KGE above 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison between various existing soil datasets in the context of model applicability concluded that SoilGrids250 is the current state-of-the-art soil dataset [38]. Some hydrologists have already applied it in their studies [39][40][41][42][43].…”
Section: Input Open-source Datasetsmentioning
confidence: 99%